Modeling Perceived Professional Autonomy in Chilean Journalism - Mellado-Ruiz, C (2012)
Based on a survey of 570 Chilean new media journalists, this article examines how they perceive autonomy in their everyday work, the importance they give to autonomy as a professional value, as well as the factors that influence their perceived editorial freedom. The results show that Chilean journalists acknowledge a high level of freedom in making news decisions, but that their conception of autonomy follows two different paths: while the importance given to autonomy is related to the profession s ideal of public service, their satisfaction with editorial freedom fits into a pragmatic context, associated with their professional and job development. The results also reveal that the factors that better predict professional autonomy are having an editorial position within the media, the assignment of a news beat, perceived political and organizational influences, and the media s political orientation and geographical location. Economic factors, meanwhile, do not have any direct effect on the journalists perceptions. © The Author(s) 2012.
Keywords: Chile; journalism; journalists; news media; perceived professional autonomy